2020
DOI: 10.1002/humu.23959
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis genome‐wide association study variant c.3781 C>A is regulated by a novel anti‐osteogenic factor miR‐345‐5p

Abstract: Upstream transcription factor family member 3 (USF3) c.3781C>A (rs1026364) in the 3′-untranslated region (3′-UTR) has been firmly associated with bone mineral density (BMD) in genome-wide association study (GWAS). However, the molecular mechanism by which it influences BMD and osteoporosis is unknown. Bioinformatics analyses suggested that the risk c.3781A allele creates a target site for hsa-miR-345-5pbinding. Luciferase assay validated that the c.3781A allele displayed significantly lower luciferase activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…No similar relationships were found for COL1A1. However, in hFOB1.19 cells heterozygous for the c.3781A allele and the c.3781C allele, the expression of COL1A1 was regulated by hsa-miR-345-5p, affecting ALP activity and substrate mineralization levels [ 68 ]. Hawkins et al .…”
Section: Discussionmentioning
confidence: 99%
“…No similar relationships were found for COL1A1. However, in hFOB1.19 cells heterozygous for the c.3781A allele and the c.3781C allele, the expression of COL1A1 was regulated by hsa-miR-345-5p, affecting ALP activity and substrate mineralization levels [ 68 ]. Hawkins et al .…”
Section: Discussionmentioning
confidence: 99%
“…At the mRNA level of the ceRNA network, Wang et al found that in hFOB1.19 cells which were heterozygous for the c.3781A allele and the c.3781C allele, the expression of COL1A1 was regulated by hsa-miR-345-5p and affected alkaline phosphatase activity and substrate mineralization level [30] . Research by Hawkins et al on Ewing's sarcoma found that activation of Wnt/beta-catenin signaling affects the expression level of COL1A1 [31] .…”
Section: Discussionmentioning
confidence: 99%
“…As for COL1A1, no statistically signi cant results were shown in serum samples. But, it was reported that in hFOB1.19 cells which were heterozygous for the c.3781A allele and the c.3781C allele, the expression of COL1A1 was regulated by hsa-miR-345-5p and affected alkaline phosphatase activity and substrate mineralization level [64] . In addition, Hawkins et al found that activation of Wnt/beta-catenin signaling affected the expression level of COL1A1 on Ewing's sarcoma [65] .…”
Section: Discussionmentioning
confidence: 99%